2020
DOI: 10.1039/d0cc04907g
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature and limited water activity reveal a pathway to magnesiteviaamorphous magnesium carbonate

Abstract: Forsterite carbonated in thin H2O films to magnesite via amorphous magnesium carbonate during reaction with H2O-bearing liquid CO2 at 25 °C. This novel reaction pathway contrasts with previous studies that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“… 4 A recent work demonstrated that magnesite could precipitate under low water activity but not in the bulk solution. 59 Theoretical calculation using MD and metadynamics (MetaD) revealed that certain anions and solvent molecules could facilitate the dehydration of the Mg 2+ –water complex and foster precipitation of high Mg–carbonate phases. 60 Our experimental data support this calculation result with ethanol affecting the Mg hydration shell and enhance the dehydration of the Mg 2+ –water complex.…”
Section: Discussionmentioning
confidence: 99%
“… 4 A recent work demonstrated that magnesite could precipitate under low water activity but not in the bulk solution. 59 Theoretical calculation using MD and metadynamics (MetaD) revealed that certain anions and solvent molecules could facilitate the dehydration of the Mg 2+ –water complex and foster precipitation of high Mg–carbonate phases. 60 Our experimental data support this calculation result with ethanol affecting the Mg hydration shell and enhance the dehydration of the Mg 2+ –water complex.…”
Section: Discussionmentioning
confidence: 99%
“…39 Similarly, the faster kinetics of MgCO3 precipitation measured within the nanoconfined water environments, compared to the bulk solution, was explained in terms of the reduction in coordinating water molecules (fewer than six) for Mg 2+ . 40 To quantify the ability of each additive in Table 1 to promote the Mg 2+ dehydration process, we have conducted CµMD simulations of electrolyte solutions where the separation between Mg 2+ and X nwas kept at approximately 4.5 nm by imposing a harmonic potential with a force constant of 1000 kJ.mol -1 between the magnesium and the counterion ion. This corresponds to the formation of SSHIP and allows us to evaluate the ability of solution additives to stabilize the undercoordinated Mg 2+ states.…”
Section: Resultsmentioning
confidence: 99%
“…Two eigenvectors from these analyses accounted for approximately 99.95% of the variance for all data sets, suggesting that the measured spectra can be reliably represented by two components. The first component, C1, is assigned to AMC with minimum absorbance between 715 and 770 cm –1 . The second component, C2, represents magnesite with a clear CO deformation band , between 715 and 770 cm –1 but minimal absorbance for the HOH bend of adsorbed H 2 O between 1600 and 1700 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…This MCR-ALS calculated the relative concentrations of both C1 and C2 as a function of time. The relative concentrations of C1 and C2 for the experiment at 25 °C were converted to moles of AMC and magnesite, respectively, by assuming that the experiment started with a hypothetical 1 g sample of unreacted forsterite and ended with a mole percent of forsterite consumed based on an ex situ high energy X-ray diffraction (heXRD) and pair distribution function (PDF) analyses of the postreacted sample that used a molar density for dry amorphous SiO 2 . The heXRD and PDF analyses for the experiment at 25 °C are detailed in Mergelsberg et al The heXRD and PDF analyses were not available on the postreacted samples for the experiments performed at 40 and 50 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation